2009
DOI: 10.1021/jp9091078
|View full text |Cite
|
Sign up to set email alerts
|

Induced Growth of (0001)-Oriented Hydroxyapatite Nanorod Arrays on ZnO-Seeded Glass Substrate

Abstract: The oriented growth of the hydroxyapatite (HAp) nanorod array on the glass substrate with a ZnO seed layer was investigated. The samples were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy. The HAp nanorods have a length of about 2 µm and a diameter of about 200 nm. The growth mechanism of the (0001)-oriented HAp nanorod array was attributed to the "mold effect" of the (0001)-oriented ZnO seed layer. The dissolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The possibility of obtaining HAp coatings on various metallic substrates using chelate decomposition synthesis route was first shown by Fujishiro et al [24,25]. Since then, various seeding layers on the titanium substrate have been used in order to induce controlled growth of HAp crystals [26][27][28]. In the present study, we obtained hydroxyapatite coatings composed of hexagonal rods with a c-axis orientation using the appropriate concentration of NH 4 OH directly on the titanium substrate.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The possibility of obtaining HAp coatings on various metallic substrates using chelate decomposition synthesis route was first shown by Fujishiro et al [24,25]. Since then, various seeding layers on the titanium substrate have been used in order to induce controlled growth of HAp crystals [26][27][28]. In the present study, we obtained hydroxyapatite coatings composed of hexagonal rods with a c-axis orientation using the appropriate concentration of NH 4 OH directly on the titanium substrate.…”
Section: Discussionmentioning
confidence: 80%
“…The application of the appropriate seeding layer made it possible to obtain a dense coating at a higher pH. More recently, adequate HAp crystal morphology in the coatings synthesized hydrothermally was obtained also through a suitable seeding layer [26][27][28]. Lu et al showed that the use of the glass substrate with a ZnO seed layer leads to the oriented growth of the hydroxyapatite nanorod array [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jevtic et al synthesized HA nanorods by a homogeneous precipitation process in an ultrasonic field [22]. Lu et al grew HA nanorod array on the glass substrate with a ZnO seed layer [23]. Nasiri-Tabrizi et al synthesize nanosized HA via the mechanochemical method [24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this special structure, a unique group of novel nanostructures have been synthesized by Wang's group, such as asymmetric nanocantilever arrays, piezoelectric nanobelts, nanosprings, nanorings, and crossed ZnO/MgO nanorod networks . Recently, Xu et al . found that the growth of vertical hydroxyapatite nanorod arrays onto a ZnO seed layer was induced by polar surface.…”
Section: Introductionmentioning
confidence: 99%